Architecture And Urban Planning In Uzbekistan - Akhmedov Tolqin Obidovich (Zien Journals, 2022)
The article mentions the Samanid mauzoleum in Bukhara,the Chor-Bakr mauzoleum and other architectural monuments as a shining example of the architectural monuments created by our ancestors in world architecture
Keywords: Islamxshchja tower; Ichan-kala complexes; Khudoyorkhan Palace